THE EFFECT OF GOOD CORPORATE GOVERNANCE ON THE FINANCIAL PERFORMANCE OF BUMD, WEST JAVA PROVINCIAL GOVERNMENT FINANCIAL INSTITUTIONS - Jejen Jaenudin; Nastiti RIzky Shiyammurti (Jurnal Scientia, 2023)
The low financial performance of BUMDs in West Java province has become a problem that has received intensive attention from various groups. This is because the low financial performance causes the contribution of Regional Original Income (PAD) from existing BUMDs to be low. Of course this is not worth the investment made by the provincial government or level 2 local government, where the funds come from the people who should be held accountable. Based on the results of interviews with BPKP, the Governor of West Java, the Provincial DPRD and other stakeholders, it can be concluded that the factor for the low financial performance of BUMDs in West Java is the problem with the implementation of Good Corporate Governance ( GCG). This study aims to analyze the effect of GCG (institutional ownership, audit committee and board of commissioners / supervisors) on financial performance at BUMD in West Java by using Return on Assets (ROA) as a proxy for measuring financial performance. Based on literature studies, the majority of related research is conducted on companies listed on the Indonesia Stock Exchange (IDX), companies that are included in the Corporate Governance Perception Index (CGPI) and BUMNs so that this research conducted on BUMD will provide additional references from existing ones. The method of this research is panel data regression where one has to find an appropriate estimation model. Is the dominant common effect model, fixed effect model or random effect model. After that, the chow test, lagrange multipler test and hausman test were carried out. The next stage is the normality test, multicollinearity test, heteroscedasticity test and autocoleration test. The last is the interpretation stage in the form of adjusted R Square test, F test, Partial T test, Goodness of Fit test (hypothesis test). It is hoped that this research can provide recommendations to BUMD regarding the management of Good Corporate Governance in order to produce good financial performance. In terms of the level of technology absorption, it can be concluded that this research has reached stage 3. The main challenge of this research is the availability of data from 27 cities/regencies in West Java, so that the researcher makes a roadshow scenario to each city-district for data requests if the data is not readily available. complete at the Bureau that handles BUMD at the West Java Provincial Government.